Policy agenda-setting studies: an overview of Brazilian research - Capella,Ana Cláudia Niedhardt (2020)
Abstract This article aims to present a brief reflection on the studies in the field of the public policy agenda. To this end, the text presents the main theoretical and methodological developments on the subject found in the international literature, with an emphasis on three fundamental contributions: the studies developed by Cobb and Elder in the 1970s; John Kingdon’s multiple streams model in the 1980s; and Baumgartner and Jones’ propositions from the 1990s until the present. Next, we seek to understand how policy agenda-setting studies have been developed in Brazil. To do so, we conduct a mapping of the Brazilian academic production, considering theses, dissertations, and articles published in journals between 2000 and 2018. In conclusion, we note the growing expansion of agenda studies in Brazil, and we draw attention to some of the characteristics of these works, such as the preferred policy areas and the theoretical and methodological frameworks favored by researchers, among other aspects.